Methodological considerations in PISCES 3: a randomized, placebo-controlled study of intracerebral stem cells in subjects with disability following an ischemic stroke - Laskowitz, Daniel T.; Muir, Keith W.; Savitz, Sean I.; Wechsler, Lawrence R.; Pilitsis, Julie G.; Rahimi, Scott Y.; Beckman, Richard L.; Holmes, Vincent; Chen, Peng R.; Juel, Laura; Koltai, Deborah; Kolls, Brad J. (Frontiers in Stroke, 2023)
Background and hypothesis At present, there are no medical interventions proven to improve functional recovery in patients with subacute stroke. We hypothesize that the intraparenchymal administration of CTX0E03, a conditionally immortalized neural stem cell line, linked with a standardized rehabilitation therapy regimen for the upper limb, would improve functional outcomes in patients 6–12 months after an index ischemic stroke. Study design PISCES III was designed as a multicenter prospective, sham-controlled, outcome-blinded randomized clinical trial. Eligibility required a qualifying ischemic stroke 6–12 months prior to surgical intervention. Patients must be between 35 and 75 years of age and have residual moderate or moderately severe disability (mRS 3 or 4), with the preservation of some residual upper limb movement. All patients received a standardized regimen of home physical therapy following the intervention. Study outcomes The primary outcome measure is improvement in the modified Rankin Scale (mRS) of disability at 6 months post treatment. Secondary outcomes include assessment of activities of daily living (Barthel Index), functional mobility (Timed Up and Go; Fugl Meyer Assessment), neurological impairment (NIHSS), upper limb function (Chedoke Arm and Hand Inventory), as well as patient related quality of life and global rating scales. Discussion PISCES III was designed as a randomized trial directly comparing the effects of intraparenchymal injection of a conditional stem cell line vs. sham procedure in patients with subacute stroke. This is one of the first studies of this type to include a standardized minimum rehabilitation protocol. As there are a limited number of studies evaluating invasive stem cell administration in the chronic setting of CNS injury, study design considerations are discussed.